Peningkatan Keterampilan Berbicara Menggunakan Metode Sosiodrama - Dita Puspita Ekaningtyas (Paedagogie, 2018)
This study aimed at improving speaking skill of 5th grade students of Kramat 4 elementary school using sociodrama method. This type of research is a collaborative classroom action research. This research was conducted in Kramat 4 elementary school with the subjects of the research were all students of grade V of Kramat 4 elementary school, amounting 34 students, consist of 14 male students and 20 female students. In this study, researchers used an action research design developed by Kemmis and Taggart with a spiral model. The data collection methods used were tests, observations, and documentation. The data analysis technique in this research was quantitative descriptive statistic by finding mean. The result of the research showed that learning of speaking skill by using sociodrama method can improve the speaking skill of 5th grade students of Kramat 4 elementary school. The speaking skill increased in cycle I was 7.38, from initial condition 60,35 increased to 67,73. In the second cycle increased by 16.17, from the initial condition 60.35 increased to 76.52.